Impact of Diet on Gum Health in Adults: A Prospective Cohort Study - Roula Etwati; Fars Mughrbi; Khalid Omar; Ghada Alzwaghi (AlQalam Journal of Medical and Applied Sciences, 2024)
Periodontal diseases such as gum disease and periodontitis are persistent inflammatory disease processes which are multifactorial including diet. Nutrition’s influence over periodontal disorders may result via systemic inflammation as well as oral bacterial community adaption. This study conducted to assess the relationship between dietary patterns and adult periodontal health with regards to clinical determinants and inflammation biomarkers. The analysis presented here was based on a prospective cohort study that included 300 adults, aged between 20 and 60 years, with three different nutrition patterns: group A – those consuming a lot of fruits, vegetables “group B – those with an average mixed diet and group C – those whose diet consists of high number of refined sugars and processed foods. Various parameters to periodontal health such as baseline and 6-months changes in bleeding on probing (BOP), plaque index (PI), and probing depth (PD) were evaluated. Data analysis was performed through ANOVA and regression modeling. Group A showcased remarkable improvement in the periodontal parameters as significant reductions were recorded for BOP (45.7%), PI (33.3 %), and PD (17.6%) coupled with lowered CRP (30.4%) and IL-6 (28.9%) concentrations (p < 0.001). BOP (15.3%) PI (19%) PD (11.1%) CRP (24%) and IL-6 (16.7%) levels, GA, and GAG increased for Group C as a marked deterioration was witnessed all over (p < 0.001). Strong positive correlations were found during the correlation analysis between nutrient-rich diets and improved periodontal outcomes. Proper nutrition, in particular diets enriched in vitamins and minerals, improves health of the periodontium, while those high in sugar-sweetened beverages worsen the inflammation of the periodontium. These results suggest the growing need for dietary counseling within the framework of significant periodontal disease management. أمراض اللثة مثل أمراض اللثة والتهاب اللثة هي عمليات مرضية التهابية مستمرة ومتعددة العوامل بما في ذلك النظام الغذائي. قد ينتج تأثير التغذية على اضطرابات اللثة عن طريق الالتهاب الجهازي وكذلك تكيف مجتمع البكتيريا الفموية. حاولت هذه المقالة تحديد العلاقة بين الأنماط الغذائية وصحة اللثة لدى البالغين فيما يتعلق بالمحددات السريرية والمؤشرات الحيوية للالتهابات. استند التحليل المقدم هنا إلى دراسة أترابية مستقبلية شملت 300 شخص بالغ، تتراوح أعمارهم بين 20 و60 عامًا، مع ثلاثة أنماط تغذية مختلفة: المجموعة أ - أولئك الذين يستهلكون الكثير من الفواكه والخضروات وأحماض أوميجا 3 الدهنية "الصحة". "أكلة الجوز"، والمجموعة "ب" - أولئك الذين يتبعون نظامًا غذائيًا مختلطًا متوسطًا، والمجموعة "ج" - أولئك الذين يتكون نظامهم الغذائي من كمية كبيرة من السكريات المكررة والأطعمة المصنعة. تم تقييم المعلمات المختلفة لصحة اللثة مثل خط الأساس والتغيرات لمدة 6 أشهر في النزيف عند التحقيق (BOP)، ومؤشر البلاك (PI)، وعمق التحقيق (PD). تم تقييم الالتهاب الجهازي عن طريق قياس مستوى بروتين سي التفاعلي (CRP) ومستوى إنترلوكين 6 (IL-6). تم إجراء تحليل البيانات من خلال ANOVA ونمذجة الانحدار. أظهرت المجموعة (أ) تحسنا ملحوظا في مؤشرات اللثة حيث تم تسجيل انخفاضات كبيرة في BOP (45.7٪)، PI (33.3٪)، و PD (17.6٪) إلى جانب انخفاض CRP (30.4٪) و IL-6 (28.9٪). ) تركيزات (ع <0.001). BOP (15.3%) PI (19%) PD (11.1%) CRP (24%) وIL-6 (16.7%) زادت مستويات GA وGAG للمجموعة C حيث شهد تدهورًا ملحوظًا في كل مكان (P <0.001). تم العثور على ارتباطات إيجابية قوية خلال تحليل الارتباط بين الأنظمة الغذائية الغنية بالمغذيات وتحسين نتائج اللثة. التغذية السليمة، وخاصة الوجبات الغذائية الغنية بالفيتامينات والمعادن، تحسن صحة اللثة، في حين أن تناول كميات كبيرة من المشروبات المحلاة بالسكر يؤدي إلى تفاقم التهاب اللثة. تشير هذه النتائج إلى الحاجة المتزايدة للاستشارات الغذائية في إطار إدارة أمراض اللثة بشكل كبير